Slackia exigua, an anaerobic Gram-positive rod and part of human oral microbiota associated with periprosthetic joint infection of the hip. First case and review of the literature. (April 2019) - Rieber, Heime; Frontzek, Andre; Schmitt, Hubertus
Abstract: We report on the first case of a periprosthetic joint infection with the anaerobic Gram-positive rod Slackia exigua as the causative agent. The bacterium is part of human oral microbiota and has so far mainly been associated with periodontal diseases. Highlights: First case of PJI caused by Slackia exigua, an anaerobic Gram-positive rod. The organism is part of human oral microbiota. PJI was associated with dental interventions prior to onset of symptoms. The patient did not receive antibiotic prophylaxis before dental operation. He was successfully treated with ampicillin-sulbactam.